A magyar buletin . Hungarian ID - Ferenczi, Gábor (Inforg Stúdió ; Intense Film, 2003)
Duration: 01:03:00 The filmmaker travels across Transylvania to discover the reactions of Hungarian minority in Romania towards one of the then hottest issues in internal Hungarian politics in 2002, namely, the Status Act and the related issue of the so-called Hungarian Card. Holders of the ID have access to the NHS and cultural programs when visiting Hungary, while back home - i.e. Romania, they are eligible to a monthly grant equivalent of $90 for each child studying Hungarian. The Status Act evoked controversial reactions both in Hungary and in the neighbouring countries with Hungarian minority.